1987
DOI: 10.1038/sc.1987.21
|View full text |Cite
|
Sign up to set email alerts
|

Rectal probe electrostimulation in the treatment of anejaculatory spinal cord injured men

Abstract: SummaryThis paper reviews our experience with rectal probe electroejaculation (RPE) which is part of a larger effort to determine the correlates of successful ejaculation and fertility in SCI men. RPE is performed in the outpatient clinic using specially designed rectal probes. Over the past 18 months, we have attempted RPE on 38 occasions in 12 subjects (eight paraplegics and four quadriplegics) with an age range of 23-38 years and 0'5-18 years since onset of injury. Anterograde ejaculation occurred in nine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
7

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 6 publications
0
43
0
7
Order By: Relevance
“…In the present study, pushing of spermatozoa back into the bladder by the catheter was a possibility, but 'stripping' was used to clear the semen from the urethral tract before introducing the catheter (Roussel & Austin, 1968;Halstead et al, 1987) and any residual semen in the tract could not have produced the significant numbers of spermatozoa found in the bladder. In addition, no spermatozoa were found in the bladder infúsate of one collection that produced significant numbers of spermatozoa in the ejaculated sample, indicating that 'stripping' the urethra per rectum was an effective means of removing semen from the urethra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, pushing of spermatozoa back into the bladder by the catheter was a possibility, but 'stripping' was used to clear the semen from the urethral tract before introducing the catheter (Roussel & Austin, 1968;Halstead et al, 1987) and any residual semen in the tract could not have produced the significant numbers of spermatozoa found in the bladder. In addition, no spermatozoa were found in the bladder infúsate of one collection that produced significant numbers of spermatozoa in the ejaculated sample, indicating that 'stripping' the urethra per rectum was an effective means of removing semen from the urethra.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of available data (Halstead et al, 1987) from three retroejaculatory patients reported loss of 3-50% total sperm numbers to the bladder.…”
Section: Resultsmentioning
confidence: 99%
“…1 Semen retrieval may be accomplished by rectal probe electroejaculation (EEJ), 2,3 or by penile vibratory stimulation (PVS). 4,5 Of these two methods, PVS has been recommended as ®rst line treatment due to its safety, e cacy, and low investment of time and money.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s the EEJ method was re®ned and new equipment developed by Seager. 119 EEJ is carried out with an electrical probe, which is inserted rectally and placed in contact with the rectal wall in the area of the prostate gland and the seminal vesicles. The electrical stimulation is given in a wavelike pattern with progressively increasing voltage with 1 ± 2 V increments until ejaculation occurs.…”
Section: Electroejaculation (Eej)mentioning
confidence: 99%